Catheterization for treating neurogenic lower urinary tract dysfunction in patients with multiple sclerosis: A systematic review. A report from the Neuro‐Urology Promotion Committee of the International Continence Society (ICS). Issue 8 (19th June 2018) - Tornic, Jure; Sartori, Andrea M.; Gajewski, Jerzy B.; Cox, Ashley; Schneider, Marc P.; Youssef, Nadim A.; Mordasini, Livio; Chartier‐Kastler, Emmanuel; Bachmann, Lucas M.; Kessler, Thomas M.
Abstract : Aim: To systematically assess all available evidence on efficacy and safety of catheterization for treating neurogenic lower urinary tract dysfunction (NLUTD) in patients with multiple sclerosis (MS). Methods: This systematic review was performed according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) statement. Studies were identified by electronic search of Embase, Medline, Scopus, Cochrane register (last search March 3, 2018) and by screening of reference lists and reviews. Results: After screening 7′015 articles, we included four studies (one prospective and two retrospective cohort studies, one retrospective cross‐sectional study), in which a total of 445 patients were enrolled. No randomized controlled trial was available. Catheterization substantially increased quality of life, post void residual, and incontinence episodes in all included studies. Pooling of data for meta‐analysis was not possible due to the heterogeneity of reported outcomes. Adverse events were reported in two studies only. Risk of bias and confounding was intermediate. Conclusions: Preliminary data suggests beneficial effects of catheterization on the urological outcome in patients with MS. However, although intermittent and indwelling catheterization is used frequently in daily clinical practice in the MS population, the evidence base is very limited and well‐designed, properly sampled, and powered studies are urgently needed.